2009
DOI: 10.1099/vir.0.007302-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered attenuated measles virus specifically infects and kills primary multiple myeloma cells

Abstract: The applicability of cytoreductive treatment of malignant diseases using recombinant viruses strongly depends on specific recognition of surface receptors to target exclusively neoplastic cells. A recently generated monoclonal antibody (mAb), Wue-1, specifically detects CD138 + multiple myeloma (MM) cells. In this study, a haemagglutinin (H) protein that was receptor-blinded (i.e. did not bind to CD46 and CD150) was genetically re-engineered by fusing it to a single-chain antibody fragment (scFv) derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Thus, retargeting procedures can focus on H protein modifications without significantly affecting the considerable fusogenic capacity of the virus. Accordingly, a large number of studies have shown that fully retargeted MV-Edm strains demonstrate no significant attenuation of oncolytic efficacy against cells or xenografts expressing adequate levels of target receptors [43, 45, 47, 48, 50, 55, 79]. Following identification of aminoacid residues necessary for H interaction with CD46 and SLAM [24] it was determined that full retargeting may be optimally accomplished by a single CD46-ablating substitution of tyrosine by alanine at position 481 (Y481A) and a single SLAM-ablating substitution of arginine by alanine at position 533 [24, 36, 47, 80] in combination with display of targeting ligands on the C-terminus of the H protein [36, 37, 81] (Figure 1C).…”
Section: Measles Virus Retargettingmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, retargeting procedures can focus on H protein modifications without significantly affecting the considerable fusogenic capacity of the virus. Accordingly, a large number of studies have shown that fully retargeted MV-Edm strains demonstrate no significant attenuation of oncolytic efficacy against cells or xenografts expressing adequate levels of target receptors [43, 45, 47, 48, 50, 55, 79]. Following identification of aminoacid residues necessary for H interaction with CD46 and SLAM [24] it was determined that full retargeting may be optimally accomplished by a single CD46-ablating substitution of tyrosine by alanine at position 481 (Y481A) and a single SLAM-ablating substitution of arginine by alanine at position 533 [24, 36, 47, 80] in combination with display of targeting ligands on the C-terminus of the H protein [36, 37, 81] (Figure 1C).…”
Section: Measles Virus Retargettingmentioning
confidence: 99%
“…Following identification of aminoacid residues necessary for H interaction with CD46 and SLAM [24] it was determined that full retargeting may be optimally accomplished by a single CD46-ablating substitution of tyrosine by alanine at position 481 (Y481A) and a single SLAM-ablating substitution of arginine by alanine at position 533 [24, 36, 47, 80] in combination with display of targeting ligands on the C-terminus of the H protein [36, 37, 81] (Figure 1C). Construction of a wide variety of retargeted oncolytic MV-Edm derivatives has been successfully accomplished, including viruses displaying single chain antibodies against CD38 [26, 36, 37], EGFR [36, 37, 48], EGFRvIII [36, 47], alpha-folate receptor [45], HER2/neu [43], CD20 [39, 40], CEA [58, 82], PSMA [60] and the Wue-1 ligand [79]. Retargeted oncolytic MVs have also been constructed to display the snake venom peptide echistatin [41], cyclic arginine-glycine-aspartate (RGD) [78], single-chain T cell receptors [83] as well as cytokines such as IL-13 [50] and peptide ligands to the urokinase receptor (uPAR) [55].…”
Section: Measles Virus Retargettingmentioning
confidence: 99%
See 1 more Smart Citation
“…Retargeted recombinant oncolytic measles virus derivatives used in this study (figure 1) have been characterized previously: MV-H-EGFR.scFv (MV-H6-H AALS -αEGFR) [29]; MV-H-Ech (MV-ERV) [41]; MV-H-Wue.scFv (MV-Wue) [35]. The control virus MV-Hedm will have a similar susceptibility to monoclonal anti-H antibodies and anti-MV antibodies present in human serum as oncolytic MVs tested clinically [100–103], [15] as they differ from one another only by the transgene they encode.…”
Section: Resultsmentioning
confidence: 99%
“…The ablation of receptor CD46 and SLAM binding sites limits virus attachment and entry to cells expressing the receptor for the scFv or ligand linked to H. Retargeted MV-Edm derivatives retain their oncolytic activity against xenografts expressing target receptors [2937]. A variety of scFv’s have been displayed on H against different receptors: EGFR (epidermal growth factor receptor) [29, 31]; EGFRvIII [29, 32]; HER2/neu (HER2: Human Epidermal Growth Factor Receptor 2) [38], CD20 [36, 37]; folate receptor alpha [33]; CD38 [29]; CEA (carcinoembryonic antigen) [39], prostate-specific membrane antigen (PSMA) [40] and an unidentified receptor over-expressed on multiple myeloma cells that can be targeted by Wue scFv [35]. Ligands linked to H have also successfully redirected entry, for example: amino-terminal fragment of urokinase plasminogen activator (uPA) targeting uPA receptor on breast tumors and tumor stroma [34]; snake venom peptide echistatin, targeting integrins αvβ3 and α5β1 expressed on vascular endothelium [41]; single-chain T-cell receptor (scTCR) targeting a specific peptide/MHC complex [42] and interleukin-13 targeting gliomas [30].…”
Section: Introductionmentioning
confidence: 99%